Teenage Mutant Ninja Turtles/Ghostbusters. Volume 3 - Burnham, Erik; Waltz, Tom (Spotlight ; IDW, 2017)
The Ghostbusters and Teenage Mutant Ninja Turtles team up to face Chi-You in Chinatown, where a new puppet brings some serious danger.